Ultra-high-performance liquid chromatography profiling method for chemical screening of proanthocyanidins in Czech hops - Olšovská, J; Kameník, Z; Čejka, P; Jurková, M; Mikyška, A (Talanta, 2013)
Hops represent an important natural source of bioactive polyphenols, particularly proanthocyanidins, which can contribute to prevention of several civilization diseases, owing to their antioxidant and radical scavenging activity. We have developed a high-throughput ultra-high-performance liquid chromatography time-of-flight mass spectrometry profiling method, which can be used for monitoring of bioactive proanthocyanidins in hops. The method was applied for analysis of hops of four Czech varieties (Saaz, Sladek, Preminat and Agnus) from the 2011 crop (9 localities, 11 samples) and the 2012 crop (24 localities, 40 samples). Hop samples were extracted by acetone and the analytes were separated on the Acquity UPLC BEH Shield RP18 column. Partial validation of the method revealed a satisfactory intra-day repeatability of the method for retention times (relative standard deviation within 1.39%) as well as areas under the peaks (within 9.89%). Experimental data were evaluated using principal component analysis and cluster analysis. Significant amounts of di-, tri- and tetramer proanthocyanidins consisting of (epi)catechin and (epi)gallocatechin were found in the hop samples. The dependence of the proantocyanidin composition on both the variety and the growing locality was observed. Specifically, the traditional Saaz variety contained more frequently oligomers formed by (epi)catechin units only, whereas the varieties Premiant and Agnus produced oligomers consisting of (epi)catechin as well as (epi)gallocatechin units. The relative abundance of proanthocyanidins in studied hop varieties from the two crops, 2011 and 2012, did correspond to each other. In the further perspective, the method may also be used for prediction of qualitative marks or authenticity verification of hops.
Keywords: aceton; shluková analýza; Cluster Analysis; Humulus; rozpouštědla; katechin; rychlé screeningové testy; reprodukovatelnost výsledků; Czech Republic; Česká republika; Proanthocyanidins; Catechin; proantokyanidiny; Chromatography, High Pressure Liquid; Acetone; Solvents; vysokoúčinná kapalinová chromatografie; analýza hlavních komponent; Principal Component Analysis; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Reproducibility of Results; High-Throughput Screening Assays; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization